A texture-enhanced α-Al2O3 coated tool and preparation method thereof
By optimizing the crystal growth direction and multi-layer coating structure in the α-Al2O3 coating, the problem of insufficient wear resistance and impact resistance of existing coatings is solved, and higher wear resistance and collapse resistance are achieved, and the Cutting life.
Patent Information
- Application Number
- CN202411382984.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing α-Al2O3 coatings lack wear resistance and impact resistance during high-speed cutting, resulting in short cutting life, and the crystal growth orientation is not conducive to the neat arrangement of the coating and the improvement of impact resistance.
The α-Al2O3 coating was deposited by CVD method, and it was divided into four parts from the inside to the outside along the thickness direction. The angle between the <001> crystal direction of each part and the normal of the coating surface gradually decreased, and combined with the multi-layer coating structure , including TiN, MT-Ti(CxNyOz), (Ti1-wAlw) (CaNbOc) and TimOn layers, optimize the crystal growth direction and grain distribution, and improve the texture coefficient and hardness of the coating.
It significantly improves the wear and collapse resistance of the tool, extends the cutting life, and shows excellent cutting performance in steel parts turning.
Smart Images

Figure CN118880276B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mechanical processing tools, and in particular relates to a texture-strengthened alpha-Al2O3 coating tool and a preparation method thereof. Background Art
[0002] In order to improve the thermal stability, wear resistance and high temperature resistance of cemented carbide tools, coating treatment is usually performed on the surface of cemented carbide substrates. In the field of modern machining, in order to meet the requirements of high production efficiency and environmental protection, as well as to cope with the trend of complexity and diversification of processed materials, the wear resistance of tool coatings must be further improved. In order to meet the needs of high-speed dry cutting, current tool materials, especially tool coating materials, must further improve the high-temperature wear resistance of coating materials.
[0003] Al2O3 has excellent mechanical properties, thermal stability and oxidation resistance, and has good resistance to rake face wear, so it is considered to be an ideal material for tool coatings for metal high-speed cutting. At present, the main technical means for producing high-quality Al2O3 coatings is the CVD (chemical vapor deposition) method. Three different crystal forms of Al2O3 coatings can be obtained by the CVD method, namely α-Al2O3, κ-Al2O3 and γ-Al2O3. Among them, α-Al2O3 is the only stable Al2O3 phase and is often used in the processing of steel, cast iron and stainless steel materials.
[0004] Due to the anisotropy of the crystal, the crystal orientation of the α-Al2O3 coating has a very important influence on its cutting performance. This patent application with the publication number CN1939715A finely treats the alumina nucleation layer in the form of pulse gas, and prepares the (006) textured α-Al2O3 coating by adjusting the alumina deposition process parameters. The coating has stronger wear resistance and toughness, and can greatly improve the cutting life.
[0005] In recent years, with the improvement of cutting speed and efficiency in the machining industry, it is necessary to further improve the wear resistance and impact resistance of α-Al2O3 coatings. Due to the coarse grains of MT-TiCN coatings, the nucleation surface of α-Al2O3 has a large degree of undulation, which is not conducive to the directional growth of columnar crystals of α-Al2O3 coatings along the vertical substrate surface, thereby affecting the neat arrangement of columnar crystals of α-Al2O3 coatings, resulting in reduced wear resistance of the coating. The angle between the α-Al2O3 (110) crystal plane and the (012) crystal plane is 32.4°; the angle between the α-Al2O3 (012) crystal plane and the (104) crystal plane is 19.4°; the angle between the α-Al2O3 (104) crystal plane and the (006) crystal plane is 38.2°; the angle between the (006) crystal plane and the (110) crystal plane is 90°. During the nucleation process of α-Al2O3, the (110) orientation is easily formed. If a (006) oriented α-Al2O3 coating is directly grown on this basis, the sudden change in the crystal growth orientation is not conducive to improving the impact resistance of the coating. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the main purpose of the present invention is to propose a texture-strengthened α-Al2O3 coated tool and a preparation method thereof. The tool has both wear resistance and impact resistance, and exhibits better cutting performance and longer cutting life in turning steel parts.
[0007] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0008] A texture-strengthened α-Al2O3 coated tool, comprising a tool substrate and a coating on the substrate;
[0009] The coating comprises at least one α-Al2O3 coating deposited by a CVD method, wherein the α-Al2O3 coating has a thickness of 1.3 to 23 μm and comprises four parts from the inside to the outside in the thickness direction:
[0010] The thickness of the first part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 70-90° accounts for more than 70%;
[0011] The thickness of the second part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 45-70° accounts for more than 70%;
[0012] The thickness of the third part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 15-45° accounts for more than 70%;
[0013] The thickness of the fourth part is 1~20μm, of which <001> The area of grains whose angle between the crystal orientation and the coating surface normal is between 0 and 15° accounts for more than 70%.
[0014] As a preferred solution of the texture-strengthened α-Al2O3 coated tool described in the present invention, the change in the crystal growth direction of adjacent parts of the α-Al2O3 coating does not exceed 40°.
[0015] As a preferred embodiment of the texture-strengthened α-Al2O3 coated tool described in the present invention, the α-Al2O3 coating as a whole presents a microstructure that preferentially grows in the (006) direction, and its texture coefficient is greater than 5.
[0016] As a preferred embodiment of the texture-strengthened α-Al2O3 coated tool described in the present invention, the α-Al2O3 coating has a columnar crystal structure perpendicular to the coating surface, the coating grain size is less than 2 μm, and the hardness is greater than 27 GPa.
[0017] As a preferred embodiment of a texture-strengthened α-Al2O3 coated tool according to the present invention, the tool substrate material is cemented carbide, titanium-based carbonitride or ceramic material, and the coating is distributed in six layers from the substrate to the outside in sequence:
[0018] The first layer includes one or more layers selected from TiN or TiC, with a thickness of 0.1 to 2 μm;
[0019] The second layer is MT-Ti(C x N y O z ) coating, thickness is 1~15μm;
[0020] The third layer is (Ti 1-w Al w )(C a N b O c ) coating, thickness is 0.1μm~0.5μm;
[0021] The fourth layer is Ti m O n Coating, thickness 0.3~2nm;
[0022] The fifth layer is the above-mentioned α-Al2O3 coating with a thickness of 1.3~23μm;
[0023] The sixth layer is a TiN coating with a thickness of 0.1~2μm.
[0024] As a preferred embodiment of the texture-strengthened α-Al2O3 coated tool of the present invention, wherein: the MT-Ti(C x Ny O z ) layer has a surface roughness of less than 200 nm, where x+y+z=1, 0.5≤x≤0.9, 0.1≤y≤0.5, and 0≤z≤0.05.
[0025] As a preferred embodiment of a texture-strengthened α-Al2O3 coated tool according to the present invention, wherein: the (Ti 1- w Al w )(C a N b O c ) layer has a nano needle-like or sheet-like structure, wherein w<0.2, 0≤a≤0.5, 0≤b≤0.5, 0<c≤0.5, a+b+c=1, and the Al element and the O element show a gradient increasing change from the inside to the outside.
[0026] As a preferred embodiment of the texture-enhanced α-Al2O3 coated tool of the present invention, wherein: the Ti m O n The layer has a coherent or semi-coherent interface structure with the α-Al2O3 layer, where m≠n.
[0027] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:
[0028] A method for preparing the above-mentioned texture-strengthened α-Al2O3 coated tool comprises:
[0029] At least one α-Al2O3 coating is deposited by CVD method:
[0030] The first part of the α-Al2O3 coating is prepared by introducing a mixed gas of 1.98-2.42 vol% AlCl3, 5.20-5.38 vol% CO2, 0-0.30 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar;
[0031] The second part of the α-Al2O3 coating is prepared by introducing a mixed gas of 2.58-3.12 vol% AlCl3, 4.89-5.12 vol% CO2, 0.30-0.60 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar;
[0032] The preparation method of the third part of the α-Al2O3 coating is as follows: at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar, a mixed gas of 3.21-3.72 vol% AlCl3, 4.69-4.88 vol% CO2, 0.60-0.90 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 is introduced;
[0033] The preparation method of the fourth part of the α-Al2O3 coating is as follows: at a deposition temperature of 950~1050℃ and a deposition pressure of 50~200mbar, a mixed gas of 3.78~4.12vol% AlCl3, 4.46~4.68vol% CO2, 0.90~1.2vol% H2S, 2.11~3.24vol% HCl and the remainder H2 is introduced.
[0034] As a preferred embodiment of the method for preparing the texture-strengthened α-Al2O3 coated cutting tool of the present invention, the coating is post-treated by wet sandblasting or polishing so that the surface roughness of the coating Ra is less than or equal to 0.6 μm.
[0035] The beneficial effects of the present invention are as follows:
[0036] The present invention provides a texture-strengthened α-Al2O3 coated tool and a preparation method thereof, wherein the coating comprises at least one layer of α-Al2O3 coating deposited by a CVD method, and the coating has α-Al2O3 crystals from the inside to the outside. <001> The angle between the crystal orientation and the coating surface normal gradually decreases. The α-Al2O3 coated tool with this crystal growth orientation gradient shows excellent wear resistance and fracture resistance in steel turning. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0038] Figure 1 is a scanning electron microscope image of the coating surface of sample A of the present invention;
[0039] Figure 2 The SEM image and EBSD inverse pole figure of the coating fracture surface of sample A of the present invention are shown in FIG.
[0040] Figure 3 is the XRD diffraction pattern of sample A from the present invention;
[0041] Figure 4is the edge wear diagram of sample A of the present invention;
[0042] Figure 5 This is the edge wear diagram for comparison with sample D.
[0043] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0044] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] According to one aspect of the present invention, the present invention provides the following technical solution:
[0046] A texture-strengthened α-Al2O3 coated tool, comprising a tool substrate and a coating on the substrate;
[0047] The coating comprises at least one α-Al2O3 coating deposited by a CVD method, wherein the α-Al2O3 coating has a thickness of 1.3 to 23 μm and comprises four parts from the inside to the outside in the thickness direction:
[0048] The thickness of the first part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 70-90° accounts for more than 70%;
[0049] The thickness of the second part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 45-70° accounts for more than 70%;
[0050] The thickness of the third part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 15-45° accounts for more than 70%;
[0051] The thickness of the fourth part is 1~20μm, of which <001> The area of grains whose angle between the crystal orientation and the coating surface normal is between 0 and 15° accounts for more than 70%.
[0052] Preferably, the crystal growth direction of adjacent parts of the α-Al2O3 coating changes by no more than 40°.
[0053] Preferably, the α-Al2O3 coating as a whole presents a microstructure that preferentially grows in the (006) direction, and its texture coefficient is greater than 5; the texture coefficient is defined as follows:
[0054]
[0055] Where:
[0056] I(hkl) is the reflection intensity of the (hkl) crystal plane measured by X-ray diffraction;
[0057] I0 is the standard intensity of the diffracted reflection according to PDF card number 46-1212;
[0058] n is the number of reflection crystal planes used in the calculation;
[0059] The (hkl) reflection crystal planes used are (012), (104), (110), (006), (113), (116), and (300).
[0060] Preferably, the α-Al2O3 coating has a columnar crystal structure perpendicular to the coating surface, the coating grain size is less than 2 μm, and the hardness is greater than 27 GPa.
[0061] Preferably, the tool substrate material is cemented carbide, titanium-based carbonitride or ceramic material, and the coating is distributed in six layers from the substrate to the outside in sequence:
[0062] The first layer includes one or more layers selected from TiN or TiC, with a thickness of 0.1 to 2 μm;
[0063] The second layer is MT-Ti(C x N y O z ) coating, thickness is 1~15μm;
[0064] The third layer is (Ti 1-w Al w )(C a N b O c ) coating, thickness is 0.1μm~0.5μm;
[0065] The fourth layer is Ti m O n Coating, thickness 0.3~2nm;
[0066] The fifth layer is the above-mentioned α-Al2O3 coating with a thickness of 1.3~23μm;
[0067] The sixth layer is a TiN coating with a thickness of 0.1~2μm.
[0068] Preferably, the MT-Ti(C x N y O z) layer has a surface roughness of less than 200 nm, where x+y+z=1, 0.5≤x≤0.9, 0.1≤y≤0.5, and 0≤z≤0.05.
[0069] Preferably, the (Ti 1-w Al w )(C a N b O c ) layer has a nano needle-like or sheet-like structure, wherein w<0.2, 0≤a≤0.5, 0≤b≤0.5, 0<c≤0.5, a+b+c=1, and the Al element and the O element show a gradient increasing change from the inside to the outside.
[0070] Preferably, the Ti m O n The layer has a coherent or semi-coherent interface structure with the α-Al2O3 layer, where m≠n.
[0071] According to another aspect of the present invention, the present invention provides the following technical solution:
[0072] A method for preparing the above-mentioned texture-strengthened α-Al2O3 coated tool comprises:
[0073] At least one α-Al2O3 coating is deposited by CVD method:
[0074] The first part of the α-Al2O3 coating is prepared by introducing a mixed gas of 1.98-2.42 vol% AlCl3, 5.20-5.38 vol% CO2, 0-0.30 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar;
[0075] The second part of the α-Al2O3 coating is prepared by introducing a mixed gas of 2.58-3.12 vol% AlCl3, 4.89-5.12 vol% CO2, 0.30-0.60 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar;
[0076] The preparation method of the third part of the α-Al2O3 coating is as follows: at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar, a mixed gas of 3.21-3.72 vol% AlCl3, 4.69-4.88 vol% CO2, 0.60-0.90 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 is introduced;
[0077] The preparation method of the fourth part of the α-Al2O3 coating is as follows: at a deposition temperature of 950~1050℃ and a deposition pressure of 50~200mbar, a mixed gas of 3.78~4.12vol% AlCl3, 4.46~4.68vol% CO2, 0.90~1.2vol% H2S, 2.11~3.24vol% HCl and the remainder H2 is introduced.
[0078] Preferably, the coating is post-treated by wet sandblasting or polishing to make the coating surface roughness Ra≤0.6 μm.
[0079] The coating surface and fracture morphology were observed using a Zeiss-Supra 55 field emission scanning electron microscope (FE-SEM). Before observation, the coating sample was ultrasonically cleaned and dried to remove surface contaminants. Subsequently, the sample was fixed on the SEM sample stage using conductive glue to ensure good conductivity of the sample and reduce charging effects during electron beam scanning. Next, the sample was placed in the SEM sample chamber and the vacuum pump was started to evacuate to 1×10 -5 mbar or less to meet observation requirements. Secondary electron (SE) mode is used to observe sample surface details.
[0080] To study the texture of α-Al2O3 coating, X-ray diffraction (XRD) was performed on the tool flank using a Bruker D8 diffractometer. The coated tool was mounted in a sample holder to ensure that the flank of the sample was parallel to the reference surface of the sample, and the flank was adjusted to an appropriate height. Cu-Kα radiation was used for measurement, with a voltage of 40 kV and a current of 40 mA, and the diffraction intensity of the coated cutting tool was scanned over an incident angle range of 20° to 90°. The texture coefficient (TC) was calculated according to the Harris formula and the standard intensity PDF card. In addition, the texture of the coating was measured using the electron backscatter diffraction (EBSD) technique using a specific detector (Oxford Nordlys Max3) mounted on the SEM. Before the EBSD test, the sample coating surface was argon ion polished to ensure that the electron beam could produce a clear diffraction pattern. The electron beam was scanned over the surface of the coating with a step size of 0.05 μm, and the diffraction pattern reflected from different grains was recorded. The diffraction pattern produced by each grain is called a Kikuchi pattern. This can be used to determine the precise orientation of the crystals in that area. Finally, the orientation data of a large number of grains is analyzed using Channel 5 software, and an inverse pole figure is constructed to obtain the texture information of the coating.
[0081] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0082] As described in the present invention, 6 layers of coating are applied on the CNMG 120408E-PD3 insert of the cemented carbide indexable insert by CVD technology, the cemented carbide composition is 8.2% Co, 4.5% cubic carbide, 0.6% TiN and the balance WC, the thickness of these 6 layers is about 19 μm, and they are composed of TiN (about 0.5 μm), MT-TiCN (about 9.0 μm), TiAlOCN (about 0.5 μm), Ti2O3 (about 1 nm), α-Al2O3 (about 9.0 μm) and TiN (about 0.3 μm), wherein TiN is an optional coating. The four types of samples are respectively referred to as sample A (Example 1), sample B (Example 2), sample C (Example 3) and sample D (Comparative Example 1). The process parameters for the deposition of each sample are shown in the following table.
[0083] Table 1 Process parameters for coating preparation of sample A
[0084]
[0085] Table 2 Process parameters for coating preparation of sample B
[0086]
[0087] Table 3 Process parameters for coating preparation of sample C
[0088]
[0089] Table 4 Process parameters for coating preparation of sample D
[0090]
[0091] The surface and fracture of the α-Al2O3 coating of the sample were observed using a scanning electron microscope. The SEM surface and fracture of sample A are shown in Figure 2. Figure 1 and Figure 2 As shown in (a).
[0092] EBSD observation was performed on the polished cross section of the sample coating. The inverse pole figures of each part of α-Al2O3 of sample A and the schematic diagram of 3D unit cell orientation are shown in the figure below. Figure 2 As shown in (b), 1, 2, 3, and 4 represent the first part of the α-Al2O3 coating, the second part of the α-Al2O3 coating, the third part of the α-Al2O3 coating, and the fourth part of the α-Al2O3 coating, respectively. Figure 2 As can be seen in (b), the crystals of the first to fourth parts of the α-Al2O3 coating <001> The angle between the crystal orientation and the coating surface normal gradually decreases. The change in the crystal orientation angle between adjacent parts is less than 40°.
[0093] Detect the XRD diffraction peak texture coefficient of the sample. The XRD diffraction pattern of sample A is as follows: Figure 3 As shown, the α-Al2O3 diffraction peak of sample A presents a very strong (006) peak, accompanied by weaker (110) peak, (012) peak and (104) peak. Table 5 lists the 2θ values of the α-Al2O3 peak of sample A.
[0094] Table 5 2θ values of α-Al2O3 peak of sample A
[0095]
[0096] Table 6 lists the texture coefficient (TC) of each diffraction peak of each sample after calculation.
[0097] Table 6 Sample texture coefficient (TC)
[0098]
[0099] In terms of coating performance, the cutting performance of each sample is compared through continuous and intermittent turning of steel parts.
[0100] Experiment 1:
[0101] Operation: Continuous Turning
[0102] Workpiece: cylindrical parts
[0103] Material: 4340 alloy steel
[0104] Blade type: CNMG 120408E-PD3
[0105] Cutting speed: 300 m / min
[0106] Feed: 0.2 mm / rev
[0107] Cutting depth: 2.0 mm
[0108] Wet / Dry Cutting: Dry Cutting
[0109] The wear volume VB (unit: mm) measured after cutting for 5 minutes, 10 minutes, 15 minutes and 20 minutes is shown in the table below.
[0110] Table 7 Wear volume VB after continuous cutting for 4 minutes, 8 minutes, 12 minutes and 16 minutes (unit: mm)
[0111]
[0112] It can be seen from Table 7 that the tool of the present invention greatly improves the wear resistance of the coating. During the cutting process, the crater wear of samples A, B and C is less than that of sample D at each time point. Figure 4 and Figure 5 These are SEM images of tool tip wear after 8 minutes of cutting for sample A and sample D. The wear of sample D is much greater than that of sample A.
[0113] Experiment 2:
[0114] Operation: Interrupted turning
[0115] Workpiece: Slotted cylindrical parts
[0116] Material: 4340 alloy steel
[0117] Blade type: CNMG 120408E-PD3
[0118] Cutting speed: 250 m / min
[0119] Feed: 0.25 mm / rev
[0120] Cutting depth: 2.0 mm
[0121] Wet / Dry Cutting: Wet Cutting
[0122] The wear volume VB (unit: mm) measured after 7 minutes, 14 minutes, 21 minutes and 28 minutes of cutting is shown in the following table.
[0123] Table 8 Wear volume VB after 7 minutes, 14 minutes, 21 minutes and 28 minutes of intermittent cutting (unit: mm)
[0124]
[0125] It can be seen from Table 8 that the coated cutting tool of the present invention improves the chipping resistance of the tool.
[0126] Compared with the prior art, the blade tool of the present invention has a longer tool life, whether continuous or intermittent.
[0127] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A texture-strengthened α-Al2O3 coated tool, characterized in that: Including tool substrate and coating on substrate; The coating comprises at least one α-Al2O3 coating deposited by a CVD method, wherein the α-Al2O3 coating has a thickness of 1.3 to 23 μm and comprises four parts from the inside to the outside in the thickness direction: The thickness of the first part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 70-90° accounts for more than 70%; The thickness of the second part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 45-70° accounts for more than 70%; The thickness of the third part is 0.1~1μm, <001> The area of grains with an angle between the crystal orientation and the coating surface normal of 15-45° accounts for more than 70%; The thickness of the fourth part is 1~20μm, of which <001> The area of grains whose angle between the crystal orientation and the coating surface normal is between 0 and 15° accounts for more than 70%.
2. The texture-strengthened α-Al2O3 coated tool according to claim 1, characterized in that: The crystal growth direction of adjacent parts of the α-Al2O3 coating changes by no more than 40°.
3. The texture-strengthened α-Al2O3 coated tool according to claim 1, characterized in that: The α-Al2O3 coating as a whole presents a microstructure that grows preferentially in the (006) direction, and its texture coefficient is greater than 5.
4. The texture-strengthened α-Al2O3 coated tool according to claim 1, characterized in that: The α-Al2O3 coating has a columnar crystal structure perpendicular to the coating surface, a coating grain size of less than 2 μm, and a hardness of more than 27 GPa.
5. The texture-strengthened α-Al2O3 coated tool according to claim 1, characterized in that: The tool base material is cemented carbide or ceramic material, and the coating is distributed in six layers from the base to the outside in sequence: The first layer includes one or more layers selected from TiN or TiC, with a thickness of 0.1 to 2 μm; The second layer is MT-Ti(C x N y O z ) coating, wherein x+y+z=1, 0.5≤x≤0.9, 0.1≤y≤0.5, 0≤z≤0.05, and a thickness of 1-15 μm; The third layer is (Ti 1-w Al w )(C a N b O c ) coating, wherein w<0.2, 0≤a≤0.5, 0≤b≤0.5, 0<c≤0.5, a+b+c=1, and thickness is 0.1~0.5μm; The fourth layer is Ti m O n Coating, where m≠n, thickness is 0.3~2nm; The fifth layer is the above-mentioned α-Al2O3 coating with a thickness of 1.3~23μm; The sixth layer is a TiN coating with a thickness of 0.1~2μm.
6. The texture-strengthened α-Al2O3 coated tool according to claim 5, characterized in that: The MT-Ti(C x N y O z )The surface roughness of the coating is less than 200nm.
7. The texture-strengthened α-Al2O3 coated tool according to claim 5, characterized in that: The 1-w Al w )(C a N b O c ) The coating has a nano-needle or flake structure, and the Al and O elements show a gradient increase from the inside to the outside.
8. The texture-strengthened α-Al2O3 coated tool according to claim 5, characterized in that: The Ti m O n The coating and the α-Al2O3 coating have a coherent or semi-coherent interface structure.
9. A method for preparing a texture-enhanced α-Al2O3 coated tool according to any one of claims 1 to 8, characterized in that: include: At least one α-Al2O3 coating is deposited by CVD method: The first part of the α-Al2O3 coating is prepared by introducing a mixed gas of 1.98-2.42 vol% AlCl3, 5.20-5.38 vol% CO2, 0-0.30 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar; The second part of the α-Al2O3 coating is prepared by introducing a mixed gas of 2.58-3.12 vol% AlCl3, 4.89-5.12 vol% CO2, 0.30-0.60 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar; The preparation method of the third part of the α-Al2O3 coating is as follows: at a deposition temperature of 950-1050°C and a deposition pressure of 50-200 mbar, a mixed gas of 3.21-3.72 vol% AlCl3, 4.69-4.88 vol% CO2, 0.60-0.90 vol% H2S, 2.11-3.24 vol% HCl and the balance H2 is introduced; The preparation method of the fourth part of the α-Al2O3 coating is as follows: at a deposition temperature of 950~1050℃ and a deposition pressure of 50~200mbar, a mixed gas of 3.78~4.12vol% AlCl3, 4.46~4.68vol% CO2, 0.90~1.2vol% H2S, 2.11~3.24vol% HCl and the remainder H2 is introduced.
10. The method for preparing a texture-enhanced α-Al2O3 coated tool according to claim 9, characterized in that: The coating is post-treated by wet sandblasting or polishing to make the coating surface roughness Ra ≤ 0.6 μm.
Citation Information
Cited By
Cutter sand blasting effect analysis and inspection method and wet sand blasting and elastic sand blasting treatment method
CN120862572A
